2012
DOI: 10.1039/c2dt12312f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbon-coated, porous and water-dispersive Fe3O4 nanocapsules and their excellent performance for heavy metal removal applications

Abstract: Porous Fe(3)O(4)@C nanocapsules with a diameter of about 120 nm (about 50 nm cavity) were synthesized by combining a sacrificial template method with solvothermal treatment. The N(2) adsorption-desorption isotherms reveals their mesoporous structure and large BET surface area (159.8 m(2) g(-1)). The magnetic investigation indicates their superparamagnetic nature and high saturation magnetization (55.93 emu g(-1)). The nanocapsules also exhibit negative zeta potential (-27.59 mV) and possess carboxyl groups on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…To improve the dispersion stability 27 of the nano-size iron oxides in suspension medium, surface 28 functions of magnetic iron oxide coated with polymers or inorganic 29 compounds has won increasing attention [8][9][10][11][12][13][14][15][16][17]. Deposition of 30 mesoporous carbon layers on magnetic nanoparticles is considered 31 as an effective way to inhibit the aggregation of magnetic 32 nanoparticles [18][19][20]. It has been also reported in our previous 33 publications that mesoporous carbon layer homogenously coated 34 on the surface of Fe 3 O 4 could effectively inhibit the aggregation of 35 Fe 3 O 4 nanoparticles [21].…”
mentioning
confidence: 99%
“…To improve the dispersion stability 27 of the nano-size iron oxides in suspension medium, surface 28 functions of magnetic iron oxide coated with polymers or inorganic 29 compounds has won increasing attention [8][9][10][11][12][13][14][15][16][17]. Deposition of 30 mesoporous carbon layers on magnetic nanoparticles is considered 31 as an effective way to inhibit the aggregation of magnetic 32 nanoparticles [18][19][20]. It has been also reported in our previous 33 publications that mesoporous carbon layer homogenously coated 34 on the surface of Fe 3 O 4 could effectively inhibit the aggregation of 35 Fe 3 O 4 nanoparticles [21].…”
mentioning
confidence: 99%
“…However, according to the Le Châtelier's principle, the lower solution pH can restrain the above response and the adsorption of Cu 2+ . 49 MOF-2COOH + Cu 2+ = MOF-2(COO)Cu + 2H + (4) 240 In aqueous medium, there are several kinds of other metal ions, such as Zn 2+ , Mg 2+ , Ca 2+ . Bearing these in mind, we further investigated the influence of the interfering ions in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Cheng et al [25] synthesized hollow Fe 3 O 4 -C nanomaterials that showed high Pb(II) adsorption capacity. Moreover, the hollow Fe 3 O 4 -C nanomaterials could be regenerated easily through magnetic separation at low pH.…”
Section: Hmis Removal By Adsorptionmentioning
confidence: 99%